2010
DOI: 10.1007/s10354-010-0857-3
|View full text |Cite
|
Sign up to set email alerts
|

High Intensity Training (HIT) für die Verbesserung der Ausdauerleistungsfähigkeit von Normalpersonen und im Präventions- & Rehabilitationsbereich

Abstract: Although intensive exercise protocols are commonly used in practical training and scientific studies, there is recently a great scientific discussion about "high intensity (interval) training" (HIT). New are the large amounts of studies and the more detailed knowledge about the physiological responses and adaptations to HIT in comparison to the classic high volume, low intensity endurance training. The present article summarizes the current knowledge about HIT in endurance exercise for clinical applications. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…For recreational athletes, as well as sedentary individuals and patients with chronic diseases, the recommendation has been endurance exercise of low-to-moderate intensity for 30–60 min daily or less frequent 20–60-min sessions of more vigorous exercise (Garber et al, 2011 ). However, this has changed recently and HIT is now being considered for such individuals as well (Wahl et al, 2010 ). Since the metabolic and health benefits of training are dependent on the amount of muscle employed, training both the upper- and lower-body may be beneficial, especially for untrained individuals and those with relatively little muscle mass in their lower-body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For recreational athletes, as well as sedentary individuals and patients with chronic diseases, the recommendation has been endurance exercise of low-to-moderate intensity for 30–60 min daily or less frequent 20–60-min sessions of more vigorous exercise (Garber et al, 2011 ). However, this has changed recently and HIT is now being considered for such individuals as well (Wahl et al, 2010 ). Since the metabolic and health benefits of training are dependent on the amount of muscle employed, training both the upper- and lower-body may be beneficial, especially for untrained individuals and those with relatively little muscle mass in their lower-body.…”
Section: Discussionmentioning
confidence: 99%
“…Although HIT and, in particular, SIT is commonly employed by elite athletes to enhance performance, both of these training modalities are now being recommended in some cases for recreational athletes, as well as sedentary individuals, and patients with chronic diseases (Wahl et al, 2010 ). In this context when training with the legs is not possible, or when it is an aim to include upper body training for health or performance improvements it is of interest whether training with the arms/upper body might improve endurance within a short period of time as well.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, a huge scientific debate about "high-intensity interval training" (HIIT) and "sprint interval training" (SIT) has emerged. Dependent on the subject population, it was shown that implementation of HIIT or SIT sessions can improve endurance capacity and VO 2max similarly or even more efficiently compared to highvolume, low-intensity endurance training (HVT) [1][2][3]. In this context, 4×30 sec "all-out" [4] and 4×4 min interval sessions at 90-95 % HR max [5] have been proven to be two successful SIT/HIIT protocols applied in training for different sports disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been shown, that HIT and SIT are not only useful tools in elite sports but also in terms of health prevention and rehabilitation (Wahl et al, 2010). HVT and SIT were shown to induce similar increases in muscle oxidative capacity, muscle buffering capacity and glycogen content, despite the distinct differences of these protocols (Gibala et al, 2006).…”
Section: Introductionmentioning
confidence: 99%